Characterization of Visceral Adipose Tissue Proteome Reveals Metabolic Changes and Inflammatory Signatures in Severe Obesity - Dadson, Prince; Honka, Miikka‐Juhani; Suomi, Tomi; Rokka, Anne; Kauhanen, Saila; Salminen, Paulina; Helmiö, Mika; James, Peter; Elo, Laura L.; Olkkonen, Vesa M.; Nuutila Pirjo (John Wiley & Sons, 2026)
Objective: Severe obesity poses a major public health concern due to its links with cardiometabolic complications and mortality. Visceral adipose tissue (VAT) plays a key role in these processes through distinct molecular features. This study aimed to characterize the VAT proteome of individuals with severe obesity and investigate its association with serum metabolic biomarkers.
Methods: A cross-sectional analysis was performed for 46 individuals with severe obesity undergoing metabolic bariatric surgery and 17 healthy controls undergoing elective abdominal surgery. VAT proteomes were analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS), and serum metabolites were quantified using nuclear magnetic resonance-based metabolomics.
Results: LC-MS/MS identified 22 differentially expressed proteins (FDR < 0.05) in VAT with 12 downregulated and 10 upregulated in severe obesity. Downregulated proteins included mitochondrial enzymes involved in substrate metabolism and mitochondrial transmembrane transport. Circulating glucose, valine, and isoleucine correlated negatively with VAT mitochondrial transmembrane and electron transport proteins. Upregulated proteins were associated with inflammation, immune activation, oxidative stress, cytoskeletal remodeling, and protein turnover.
Conclusions: These findings demonstrate significant molecular alterations in the VAT proteome associated with severe obesity, providing insights into the underlying mechanisms of metabolic disease. The differentially expressed proteins may serve as biomarkers or therapeutic targets for obesity-related complications.